The Application of Digital Marketing Strategies in the Localization of LED Lighting Brands in the US Market - Xueping Wei (Journal of World Economy, 2025)
With the rapid development of the global LED lighting market, the US, as a significant consumer market for LED lighting, has attracted the attention of numerous international brands. However, entering the US market and achieving brand localization is no easy task, and digital marketing strategies play a crucial role in this process. This paper aims to explore how digital marketing strategies can assist LED lighting brands in their localization in the US market. First, the paper provides an in-depth analysis of the characteristics of the US LED lighting market, including market size, growth trends, competitive landscape, and consumer behavior. It then elaborates on the specific applications and mechanisms of digital marketing tools such as search engine optimization (SEO), social media marketing, email marketing, and marketing automation in brand localization. Through multiple successful and unsuccessful case studies, the paper summarizes practical experiences of digital marketing strategies in the localization of LED lighting brands in the US market and proposes a digital marketing strategy framework tailored to the US market. This framework emphasizes key elements such as market segmentation and precise positioning, content marketing, cooperation and alliances, and customer experience optimization, aiming to provide theoretical guidance and practical references for the promotion of LED lighting brands in the US market, enhance brand visibility and market share, and achieve sustainable development.